Treatment of Goats Infected with the Lungworm Muellerius capillaris - McCraw, Bruce M. (1986)
Goats naturally infected with Muellerius capillaris were treated with ivermectin subcutaneously once or twice at the rate of 200 or 300 μg/kg body wt or with fenbendazole per os twice at 15 μg/kg body wt. Goats ceased passing larvae 11 to 20 days after treatment, and except for one doe, larvae reappeared in feces 34 to 59 days after treatment. In sections of lung of ivermectin-treated goats, adult Muellerius had swollen body walls and disrupted intestinal tracts. Granulomas, some mineralized, were present. It is suggested that immature Muellerius were not destroyed by either anthelmintic and that following destruction of the adults, immature Muellerius resumed development to the adult stage and produced more first-stage larvae. Treatment of Muellerius may be more effective if repeated after approximately a 35-day interval.